Effect of anionic polyelectrolytes on formation of hydroxyapatite particles in simulated body fluids - Takuya Sagawa; Noritaka Kako; Masatoshi Nakaya; Takaaki Izumi; Kosuke Takeda; Kazutoshi Iijima; Mineo Hashizume (Journal of Asian Ceramic Societies)
Recently, fabrication of organic-inorganic hybrid biomedical materials using biomimetic mineralization processes has received attention because it proceeds under mild conditions and biocompatible inorganic components are incorporated in the resulting hybrids. In the present study, the preparation of anionic polyelectrolyte-apatite hybrids, having potential as a biomedical material, in simulated body fluids (SBFs) was performed. Anionic polyelectrolytes such as heparin, poly(4-styrene sulfonate) (PSS), or poly(vinyl sulfate) (PVS) were added to SBFs and incubated to induce nucleation of hydroxyapatite, which resulted in the formation of anionic polyelectrolyte-apatite hybrids. Physical characterization of the resulting deposits in SBFs using scanning electron microscopy (SEM), energy-dispersive X-ray spectroscopy (EDX), FT-IR spectroscopy, and X-ray diffraction (XRD) revealed that the polyelectrolyte concentration affected the yield of the resulting deposits. It seemed that the reaction condition affected the apatite nucleation process in SBFs. Effect of chemical structures and concentrations of anionic polyelectrolytes on hybrid formation is discussed.